Implementation of Emergency Public Activity Restrictions (PPKM) in Accordance With Human Rights and Pancasila Principles - Marjan Miharja; Emil Salim; Gunawan Nachrawi; Rachmat Dwi Putranto; Anggoro Hendrawan (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
Since the beginning of 2021, the Indonesian government's policy has been to enforce public activity restrictions (abbreviated as PPKM) in order to deal with Covid-19 pandemics in Indonesia. Public activity restrictions (PPKM) are in place in various places that are hotspots for Covid-19 infection, most notably on the Indonesian island of Java and Bali. The government took this effort to slow the spread of Corona Virus, or Covid-19. Prior to the implementation of this public activity restriction (PPKM) program, the government imposed large-scale social restrictions (PSBB) or lockdown zones in a number of places throughout Indonesia. The government was fully supported in implementing these public activity restrictions (PPKM) by the Indonesian National Armed Forces (TNI), Police, and municipal police units (Satpol PP) as part of the Covid-19 Task Force. How effective these public activity restrictions (PPKM) are remains an open question for all stakeholders. However, the reality is that there are still numerous singers between the community and the Task Force on public activity restrictions (PPKM), resulting in damage to the community and a negative influence on society. Numerous human rights breaches and actions that contradict the nation's ideology, specifically Pancasila, result in a fall in community faith in the government.